Pemberdayaan Komunitas dalam Ekowisata di Pulau Kecil: Kajian Literatur Sistematis Bibliometrik-Analisis Konten (2014-2024) - Nurhasanah, Isye Susana; Angely, Graciela; Rahman, M. Bobby (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2025)
Small islands possess significant potential as ecotourism destinations; however, they also face various limitations, including restricted land area, inadequate infrastructure, and isolation from other regions. These conditions often lead to resource exploitation by certain parties without considering sustainability. Therefore, the role and capacity of human resources (HR) are crucial, supported by collaboration among the government, stakeholders, and local communities to ensure sustainable management. This study analyzes community empowerment on small islands through a Systematic Literature Review (SLR) and bibliometric analysis to identify key themes and research gaps. The study also evaluates the extent to which this aspect has been discussed in previous research and reveals existing gaps. The literature analyzed includes publications from the past ten years (2014-2024), sourced from the Publish or Perish (PoP) database. The findings indicate that although community empowerment has been widely discussed in the literature, studies specifically focusing on the context of small islands remain limited. Several aspects, such as the impact of climate change and political dynamics in community-based ecotourism management, have not been extensively examined and represent research gaps that warrant further exploration in future studies. Findings highlight the need for further studies on climate change impacts and governance in community-based ecotourism.